Regionale Verteilung öffentlicher Mittel für Universitäten: Zum Einfluss unterschiedlicher Verfahren der Hochschulfinanzierung auf die regionale Ressourcenverteilung — Die Beispiele Niederlande, Großbritannien und Texas - Liefner, Ingo (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Public funding of institutions of higher education affects regions as the spending of universities creates demand and fosters regional development. This article analyzes the nonintended regional effects of public funding of universities. Examples are the Netherlands, Britain and the US. These countries are currently viewed as being role models for reforms in the German higher education system. It can be shown that specialization of universities and competition for public resources leads to regional concentration of resources. The use of stabilizing factors in the funding process can limit regional redistribution.